AB0259 Anti-Carbamylated Protein (ANTI-CARP) Antibodies Are Present in the Sera of Individuals at Different Stages of the Inflammatory Arthritis Continuum. (10th June 2014) - Hunt, L.; Verheul, M.; Nam, J.L.; Trouw, L.; Fechtenbaum, M.; Rakieh, C.; Hensor, E.M.; Toes, R.; Buch, M.H.; Emery, P.
Abstract : Background: In inflammatory arthritis (IA) the spectrum varies from individuals "at-risk" to the full rheumatoid arthritis phenotype. ACPA are highly specific for RA and associated with severe progression. Recently, anti-carbamylated protein (anti-CarP) antibodies have been identified in the sera of individuals with RA and prior to diagnosis, predicting a risk of persistence and possibly a more severe disease course [1, 2]. Objectives: To assess the presence of anti-CarP antibodies at different stages of the IA continuum; to establish association with other antibodies; to evaluate its role in diagnosis and association with disease progression. Methods: 647 individuals were assayed for anti-CarP. This included individuals who were ACPA positive with arthralgia but no clinical synovitis, individuals with IA signs and/or symptoms, newly diagnosed RA (2010 ACR/EULAR criteria) and an established disease cohort. Anti-CarP antibodies of the IgG isotype were detected using carbamylated fetal calf serum (Ca-FCS) as the capture antigen as described before [1]. A reference range for anti-CarP positivity was determined using 205 healthy Dutch blood donors. ACPA status was determined using cyclic citrullinated-peptide 2 (CCP2) commercial assays and recommended cut offs. The anti-CarP-assay was performed by investigators not aware of the diagnosis. Results: Table 1 details Anti-CarP positivity in the 4 groups: ACPA+ arthralgia, IA symptoms, new RA and established RA; and in the latter 3 groups, Anti-CarP rates in the ACPA negative subgroups. Anti-CarP antibodies were observed in both anti-CCP positive and anti-CCP negative patients. In the ACPA+ arthralgia group, 54 (43.9%) subjects progressed to clinical inflammatory arthritis during follow-up (range 5-61months) of whom 29 (53.7%) were anti-CarP positive. 48/123 individuals had CCP titre >3x limit of normal; all but one was anti-CarP positive. On a univariable basis Anti-CarP positivity was weakly associated with progression at 12 months and progression (ever). Conclusions: Anti-CarP is present in patients at different stages of the IA continuum at variable proportions. In a proportion of ACPA negative individuals it may offer an additional marker for persistent disease. Correlation with disease activity will determine the clinical utility of this test in an inflammatory arthritis clinic. References: Shi J, Knevel R, Suwannalai P, van der Linden MP, Janssen GM, van Veelen PA, et al. Autoantibodies recognizing carbamylated proteins are present in sera of patients with rheumatoid arthritis and predict joint damage. Proceedings of the National Academy of Sciences of the United States of America. 2011 Oct 18; 108(42):17372-17377. Shi J, van de Stadt LA, Levarht EW, Huizinga TW, Hamann D, van Schaardenburg D, et al. Anti-carbamylated protein (anti-CarP) antibodies precede the onset of rheumatoid arthritis. Annals of the rheumatic diseases. 2013 Dec 13. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2577